Magnetic field distortion detector / Mohammad Rizal Mohd Noor - Mohd Noor, Mohammad Rizal (1999)
It is essential for developers and users to detect the distortion of any magnetic field. This project presents the development of an ultrasensitive magnetic field distortion detector system. The system consists of sensor, voltage limiting circuit, amplifier and speaker. Other application will be in military as a radar replacement, it may also be used in power system engineering environments like detector of underground wire cable. Major magnetic disturbances caused by heavy solar activity are therefore obviously easily detected. The hardware designed is presented and the empirical experiment had been carried to compare with the theoretical results. This development is able to detect any magnetic field emitted by ferrous object.